2014
DOI: 10.1128/jcm.03308-13
|View full text |Cite
|
Sign up to set email alerts
|

Testing and Genotyping of High-Risk Human Papillomavirus by the cobas HPV Test and the Hybrid Capture 2 High-Risk HPV DNA Test Using Cervical and Vaginal Samples

Abstract: cThe accurate detection and typing of high-risk human papillomavirus (HPV) are critical for cervical cancer screening. The Hybrid Capture 2 (hc2) and cobas HPV tests showed high agreement for cervical samples (94.4%, ‫؍‬ 0.72, n ‫؍‬ 693) and moderate agreement for vaginal samples ( ‫؍‬ 0.62, n ‫؍‬ 108). The HPV16 and HPV18 results were highly consistent between the cobas and Linear Array tests ( > 0.96, n ‫؍‬ 197). Three hc2-negative vaginal samples were repeatedly invalid by the cobas test due to ␤-globin con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The concordance rate between the two assays was 84.5% with a kappa value of 0.579. Whereas the result is in line with various published studies comparing HC2 and other HR‐HPV screening tests, the agreement between the two tests may have been underestimated because the alkali condition of denatured HC2 samples could lead to DNA degradation through time, thus reducing the level of remaining HR‐HPV DNA for CerviHPV testing. This was also one reason that we focused our subsequent analyses mostly on the 15 HC2 positive discordant cases with RLU/CO values greater than 3.0.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The concordance rate between the two assays was 84.5% with a kappa value of 0.579. Whereas the result is in line with various published studies comparing HC2 and other HR‐HPV screening tests, the agreement between the two tests may have been underestimated because the alkali condition of denatured HC2 samples could lead to DNA degradation through time, thus reducing the level of remaining HR‐HPV DNA for CerviHPV testing. This was also one reason that we focused our subsequent analyses mostly on the 15 HC2 positive discordant cases with RLU/CO values greater than 3.0.…”
Section: Discussionsupporting
confidence: 86%
“…cobasHPV also employs multiplex qPCR to detect the same set of 14 HR‐HPV with the ability to genotype HPV16 and 18, and also include a cellular control to avoid false negative results. Multiple studies have demonstrated comparable performance of cobasHPV and HC2 tests to detect HR‐HPV with overall agreement of 82.8% to 97.3%, similar to the agreement between CerviHPV and HC2 tests observed in this study. Thus, it would be interesting to know how CerviHPV test compares to cobasHPV test.…”
Section: Discussionsupporting
confidence: 85%
“…Denaturant (150 µl; digeneHC2HPVDNA detection kit; Qiagen Sciences, Inc.) was then added to the mixture. Following TCT, the residual samples were denatured by asymmetric PCR (Piko ® Thermal Cycler 96-well system; Thermo Fisher Scientific, Inc., Waltham, MA, USA) to obtain single-stranded DNA (13), which was then mixed and reacted with an RNA probe cocktail (BD Pharmingen; BD Biosciences, San Jose, CA, USA) for 13 HR-HPV oncogenic types (16,18,31,33,35,39,45, 51, 52, 56, 58, 59 and 68) to capture oncogenic HPV subtypes using DML-2000 gene hybridization amplifiers (Digene Corporation). The type of positive point HPV was determined according to the distribution pattern of HPV.…”
Section: Subjectsmentioning
confidence: 99%
“…HC2 test (Qiagen Sciences, Inc., Gaithersburg, MD, USA), a signal amplification test based on the hybridization of a RNA probe cocktail for 13 high-risk oncogenic types with the target DNA, and capture and detection of the DNA-RNA hybrid by chemiluminescence, was applied to quantitate the level of HPV DNA for its standardization approved by the USA Food and Drug Administration (13). This test was performed with 4 ml of PreservCyt samples, and then mixed with 400 µl transfer buffer (digeneHC2HPVDNA detection kit; Qiagen Sciences, Inc.).…”
Section: Subjectsmentioning
confidence: 99%
“…The pathogenesis of HPV is dependent on a number of factors, but it is now understood that certain genotypes of the virus are more closely associated with the development of severe disease, including cancer. HPV genotypes are commonly separated into two broad categories, (i) "low risk" (types 6,11,40,42,43,44,53,54,61,72,73, and 81) and (ii) "high risk" (types 16,18,31,33,35,39,45, 51, 52, 56, 58, 59, 66, and 68), based on the degree of correlation between infection and the development of cervical cancer. Among the 14 high-risk (HR) genotypes, HPV-16 and HPV-18 have been estimated to account for approximately 70% of cervical cancers (2).…”
mentioning
confidence: 99%